Functional traits and ecosystem implications in the Multiple Use Marine Protected Area Almirantazgo Sound: A baseline study of scallop banks and benthic communities - Sepulveda, Taryn; Andrade Diaz, Claudia Daniela Yanett; Almonacid, Eduardo; Daza, Erik; Rivera, Cristobal; Vargas, Cristian; Aldea Venegas, Cristian Leonardo (My University, 2024)
Amid escalating environmental challenges confronting marine ecosystems, the proliferation of coastal and marine protected areas (MPAs) has emerged as a pivotal strategy for mitigating biodiversity loss and fostering sustainable resource management. This research advocates for a paradigm shift towards a trait-based approach to assess functional diversity (FD) within MPAs, with a specific focus on the ecologically crucial Austrochlamys natans banks in Parry Bay, MPA Almirantazgo Sound. By surveying 28 invertebrate species across eight phyla, a PCA using fuzzy-coded functional traits revealed five distinct groupings primarily based on feeding, movement, and reproductive modes. Mobile predators and scavengers clustered distinctly from sessile suspension feeders and limited-mobility grazers, indicating a scarcity of mobile predator species in Parry Bay, which impacts the ecosystem's dynamics. FD indices highlighted low functional alpha-diversity, emphasizing trait redundancy that enhances resilience but relies heavily on a few unique and specialized species. The potential extinction or migration of these species could directly affect unique ecosystem properties. While revealing the resilience of the benthic community, this research underscores its dependence on a handful of species that are crucial for both ecological functions and regional commercial significance. Urgent conservation and management measures are imperative to protect these species and maintain the delicate balance of this ecosystem.
Keywords: fisheries management; biological traits; functional diversity; suspension feeders; functional uniqueness; patagonian fjords